Occurrence of Soil Fungi in Antarctic Pristine Environments - Durán, Paola; Barra, Patricio J.; Jorquera, Milko A.; Viscardi, Sharon; Fernandez, Camila; Paz, Cristian; Mora, María de la Luz; Bol, Roland (Frontiers in Bioengineering and Biotechnology, 2019)
The presence of fungi in pristine Antarctic soils is of particular interest because of the diversity of this microbial group. However, the extreme conditions that coexist in Antarctica produce a strong selective pressure that could lead to the evolution of novel mechanisms for stress tolerance by indigenous microorganisms. For this reason, in recent years, research on cold-adapted microorganisms has increased, driven by their potential value for application in biotechnology. Cold-adapted fungi, in particular, have become important sources for the discovery of novel bioactive secondary metabolites and enzymes. In this study, we studied the fungal community structure of 12 soil samples from Antarctic sites, including King George Island (including Collins Glacier), Deception Island and Robert Island. Culturable fungi were isolated and described according to their morphological and phenotypical characteristics, and the richness index was compared with soil chemical properties to describe the fungal community and associated environmental parameters. We isolated 54 fungal strains belonging to the following 19 genera: Penicillium, Pseudogymnoascus, Lambertella, Cadophora, Candida, Mortierella, Oxygenales, Geomyces, Vishniacozyma, Talaromyces, Rhizopus, Antarctomyces, Cosmospora, Tetracladium, Leptosphaeria, Lecanicillium, Thelebolus, Bjerkandera and an uncultured Zygomycete. The isolated fungi were comprised of 70% Ascomycota, 10% Zygomycota, 10% Basidiomycota, 5% Deuteromycota and 5% Mucoromycota, highlighting that most strains were associated with similar genera grown in cold environments. Among the culturable strains, 55% were psychrotrophic and 45% were psychrophilic, and most were Ascomycetes occurring in their teleomorph forms. Soils from the Collins Glacier showed less species richness and greater species dominance compared with the rest of the sites, whereas samples 4, 7 and 10 (from Fildes Bay, Coppermine Peninsula and Arctowski Station, respectively) showed greater species richness and less species dominance. Species richness was related to the C/N ratio, whereas species dominance was inversely related to C and N content. Thus, the structure of the fungal community was mainly related to soil chemical parameters more than sample location and altitude.